Social Construction of Female Smokers Among College Students - Mochammad Dimas Putra Setyafudin; Ahmad Ridwan; Sugeng Harianto (University of Muhammadiyah Malang, 2026)
This study aims to analyze how patriarchal norms shape social stigma against female smokers among university students, given the significantly higher smoking prevalence among men in Indonesia compared to women. Gender norms influenced by this patriarchal system create a double standard that negatively stigmatizes women, such as